If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6x + 12 = -4 Reorder the terms: 12 + 8x + -6x = -4 Combine like terms: 8x + -6x = 2x 12 + 2x = -4 Solving 12 + 2x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2x = -4 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = -4 + -12 2x = -4 + -12 Combine like terms: -4 + -12 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| -3x+8y=13 | | 9e-2=16 | | 8w-91=w | | c^2-14c+40= | | x^7=36 | | 5(x-1)=20.5 | | x-4=4x-31 | | 4(a+3)=43.2 | | 5+10(a+2)=35 | | .75x+11=-1 | | 16n^2+16a+4=0 | | 6k-7=11 | | 4/3n=21/3 | | 4e-7=32.6 | | 12x+3-5x=75 | | 3x-2/7 | | 11d+4=2d+67 | | 15x+5=-40 | | 4(x+1.97)=3x | | 40+40+z=180 | | 20+d=67 | | a^2+6a+72= | | 2+9x=-3x-22 | | d-15=20 | | (16x^5/x)^-1/2 | | 9*(x-1)=27X | | 8d+4=7d+12 | | 5-2x=-4x+1 | | 2x*-3x+4=3 | | -(-5)3(-2)= | | 2(x-5)=-12(x+10)+4x | | 3(-5/2) |